A 6-Month Prospective Trial of a Personalized Behavioral Intervention + Long-Acting Injectable Antipsychotic in Individuals With Schizophrenia at Risk of Treatment Nonadherence and Homelessness. Issue 6 (December 2017) - Sajatovic, Martha; Ramirez, Luis F.; Fuentes-Casiano, Edna; Cage, Jamie; Tatsuoka, Curtis; Aebi, Michelle E.; Bukach, Ashley; Cassidy, Kristin A.; Levin, Jennifer B.
Abstract: Purpose: Long-acting injectable antipsychotics (LAI) can optimize adherence for high-risk serious mental illness (SMI). This customized adherence-enhancement approach delivered by social worker interventionists was combined with LAI (CAE-L) of paliperidone palmitate for homeless, poorly adherent individuals with SMI. Methods: This 6-month prospective, uncontrolled trial of CAE-L in 30 recently homeless individuals with SMI assessed adherence using the Tablets Routine Questionnaire, injection frequency, and SMI symptoms measured by the Positive and Negative Syndrome Scale, Brief Psychiatric Rating Scale, and Clinical Global Impressions. The Social and Occupational Functioning Assessment Scale measured social function. Standardized scales assessed extrapyramidal effects. Findings: Patients' mean age was 43.6 (SD, 9.53) years, and they were mainly minorities (86.7% African American) and single/never married (72.4%). Rate of substance abuse within the past year was 40.0%, and rate of incarceration within the past 6 months was 32.1%. Four participants (13.3%) terminated the study prematurely. Customized adherence enhancement + LAI was associated with good adherence to LAI (92.9%) and improved adherence with oral drug as measured by Tablets Routine Questionnaire ( P = 0.02). There were significant improvements in Positive and Negative Syndrome Scale ( P < 0.01), Brief Psychiatric Rating Scale ( P < 0.001), Clinical Global Impressions ( P = 0.003), and Social and Occupational Functioning Assessment Scale ( P = 0.005). There were no significant extrapyramidal effects. Implications: While findings must be tempered by the methodological limitations, CAE-L seems associated with multiple domains of improvement in homeless/recently homeless individuals with SMI. Adverse effects limit tolerability in some individuals, and not all will remain engaged. However, LAI combined with a patient-centered behavioral approach can improve outcomes for some high-risk individuals with SMI.